Evaluation and Outcome of Acute Scrotum at Gezira National Center of Pediatric Surgery and Gezira Hospital for Renal Diseases and Surgery; January 2009 to July 2012 - Mustafa, Loui Eltayeb; Nugud, Fiasal Abd Elgalil; Omran Mansur, Mustafa (مجلة الجزيرة للعلوم الصحية; مجلد 10 عدد 1 (2014), 2014)
Objective : To evaluate the clinical presentation, causes, management and outcome of patients who presented with clinical aspect of acute scrotum. Material and methods:   A total of 72 patients aged from one day to adulthood period hospitalized with acute scrotum were included in the study. Most of patients underwent surgical exploration of the scrotum, and the medical records were revised to obtain information regarding operative findings and post-operative complications.   Results : The different common causes of acute scrotal pain were testicular torsion (27.8%), epididymo-orchitis (20.8%), and torsion of testicular appendix (19.4%). The most common age group affected by the disease is between 10 and 20 years (37.5%). Approximately two-thirds of patients presented late after 24 hours of onset of pain (61.1%), and (9.2%) developed post-operative complications. Conclusion: Generally, children and teenagers are more likely to be affected by scrotal conditions, and most patients presented late. Testicular torsion was the most common and most serious condition which must be identified early without delay to prevent testicular damage. Any patient suspected to have testicular torsion must be subjected immediately to scrotal exploration. Post-operative complications were low.